# 7/3 minus 11/6 as a fraction 7/3 - 11/6 as a fraction provides the detailed information about what is 7/3 minus 11/6 in fraction and decimal form, and the answer with steps to understand how it is being calculated by using different methods.

7/3-11/6 equals to
7/3 - 11/6 = (?)
7/3 - 11/6 = [(7 x 6) - (11 x 3)]/(3 x 6)
= (42 - 33)/18
= 9/18
= (9 x 1)/(9 x 2)
= 1/2
7/3 - 11/6 = 1/2
7/3 minus 11/6 is equal to 1/2

where
7/3 is a fraction as a minuend,
11/6 is a fraction as a subtrahend,
1/2 is the difference between 7/3 and 11/6.

7/3 minus 11/6 as a decimal
7/3 - 11/6 = 1/2
1/2 = 0.5
7/3-11/6 as a decimal is 0.5
where
0.5 is the difference between 7/3 and 11/6.

For values other than 7/3 minus 11/6, use this below tool:

## How-to: 7/3 - 11/6 = ?

The below workout with step by step calculation shows how to find what is 7/3 minus 11/6 in simplest form by using the following methods:
1. LCM method,
2. Cross multiplication method.

Problem and Workout - LCM Method:
What is 7/3 minus 11/6 as a fraction?

step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 7/3
Fraction B: 11/6

What to be found?
7/3-11/6 = ?
Find what's the difference between 7/3 and 11/6.

step 2 Compare the denominators of fractions 7/3 and 11/6 to identify whether it is a like or unlike fraction subtraction. Since the denominators of given fractions 7/3 and 11/6 are not equal, it is said to be unlike fractions subtraction.

step 3For unlike fractions subtraction, find the LCM (least common multiple) of both denominators of fractions 7/3 and 11/6:
The LCM of 3 and 6 is 6.

step 4 Write the fractions 7/3 and 11/6 in the subtraction expression form and multiply LCM with all the numerators and denominators of both fractions.
=7/3-11/6
=(7 x 6)/(3 x 6)-(11 x 6)/(6 x 6)

step 5 Simplify the expression to have common denominator:
=14/6-11/6

step 6 Take the common values out and rewrite the above expression like the below:
=1/6 x (14/1-11/1)
=1/6 x (14 - 11)

step 7Simplify the above expression further:
=1/6 x 3
= 3/6
=1/2
7/3-11/6=1/2

Hence,
7/3 minus 11/6 equals to 1/2 in fraction.

Problem and Workout - Cross Multiplication Method
step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 7/3
Fraction B: 11/6

What to be found?
7/3-11/6 = ?
Find what's the difference between 7/3 and 11/6.

step 2 Find the product of numerator of Fraction A and denominator of Fraction B (7 x 6), find the product of numerator of Fraction B and denominator of Fraction A (11 x 3), and find the product of both denominators of Fraction A and Fraction B (3 x 6) and rewrite the equation as like the below:
= (7 x 6) - (11 x 3)/(3 x 6)

step 3 Simplify and rewrite the fraction:
= (42 - 33)/18
= 9/18
= 1/2
7/3-11/6 = 1/2
Hence,
7/3 minus 11/6 = 1/2 